Chiral Bicyclo[2.2.2]octane-Fused and Ferrocene-Derived Cyclopentadienyl Ligands for Asymmetric C–H Activation - Liang, Hao; Wang, Jun (Synlett, 2023)
To fulfill increasing and diverse demands of cyclopentadienyl metal complexes (CpM) catalyzed asymmetric C–H activation, innovation in developing new types of chiral Cp ligands should be important. In this context, we found the structurally rigid chiral bicyclo[2.2.2]octane-fused Cp ligands originated by Vollhardt and Halterman were efficient to enable highly enantioselective C–H activation of N-methoxybenzamides with quinones. Besides, we also designed and synthesized a class of ferrocene-based chiral Cp ligand featuring a loose chiral pocket, whose rhodium complexes exhibited high reactivity and reasonable enantioselectivity in an asymmetric intramolecular aryl amination of alkene.1 Introduction2 Chiral Cp Ligands Applied in Asymmetric C–H Activation3 Chiral Bicyclo[2.2.2]octane-Fused Cp Ligands4 Chiral Ferrocene-Derived Cp Ligands5 Conclusion
Keywords: chiral cyclopentadienyl; bicyclo[2.2.2]octane; ferrocene; rhodium; asymmetric C–H activation